Researching health promotion - Watson, Jonathan, 1960-; Platt, Stephen (Routledge, 2000)
Annotation Providing a critical review of the current state of health promotion research. This book re-conceptualises the field of health promotion as collaborative and integrating enterprise, rather than as a battlefield for disciplinary and intellectual clashes. It makes a significant contribution to ongoing epistemological, theoretical and methodological debates in health promotion research. With contributors from Sweden, Switzerland, Denmark, Ireland, the UK and the US, Researching Health Promotion will be of interest to students and professionals working in health promotion, public health, medicine and health policy.
Keywords: Health promotion -- Research.; Health promotion.; Research.; Health Promotion; Research; Promotion de la santé -- Recherche.; Promotion de la santé.; Recherche.; research (function); MEDICAL -- Preventive Medicine.; HEALTH & FITNESS -- Healthy Living.; HEALTH & FITNESS -- Reference.; HEALTH & FITNESS -- Holism.; Health promotion; Health promotion -- Research